Pengaruh filtrat cendawan Aspergillus sp. dan Fusarium sp. terhadap viabilitas benih dan pertumbuhan bibit sengon (Paraserianthes falcataria) - Naning Yuniarti; Tati Suharti; Yulianti Bramasto (Jurnal Penelitian Kehutanan Wallacea, 2013)
Fungi are one of the main causes of damage to seeds. Fungi can be a pathogen or saprophyte such as Aspergillus sp. and Fusarium sp. The purpose of this study was to determine the effects of filtrate fungus Aspergillus sp and Fusarium sp on seed viability and seedling growth performance of Sengon (Paraserianthes falcataria). The experiment design used was the Completely Randomized Design (CRD), with treatment: control, filtrate of Aspergillus sp and Fusarium sp filtrate. Each treatment was repeated 4 times. Variables measured include germination, percent of live seed, height, diameters, biomass, root shoot ratio, and the index quality seeds. The results showed that the fungus Aspergillus sp filtrate and Fusarium sp significantly affect seed germination, life percent, height, diameter, NPA, IMB, and biomass of seedlings Sengon. The filtrate of fungus Aspergillus sp and Fusarium sp may cause the decrease in seed viability and seedling vigor of Sengon